Pengaruh Kebisingan Lalu Lintas Terhadap Penurunan Fungsi Pendengaran Pada Supeltas Di Kota Surakarta - Listianingrum, Daranita Aprilia, Sri Darnoto S.KM M.PH (2017)
Supeltas that everday are on the highway and exposure to noise and traffic can to be at risk causing health problems like loss of hearing. This research aims to study the influence of traffic noise with the hearing loss of Supeltas in Surakarta city. The type of this research is kuantitatif analytic with a fisher's exact approach. The population used in this research is a man worker where so people are chosen by exhaustive sampling. Data analysis by using fisher's exact test. The result show that there is a influence between traffic noise with hearing loss of Supeltas in Surakarta city (p = 0,005<0,05).